Shear wave speed changes in the cervix and vulvar lips of Kivircik ewes before and after parturition - Günay Uçmak, Zeynep; Uçmak, Melih; Kurban, İbrahim; Özbezek, Mehmet Fatih; Ekiz, Bülent (Frontiers in Veterinary Science, 2026)
IntroductionIn recent years, the evaluation of the cervix in pregnant women using shear wave elastography (SWE) has gained attention. However, there is limited information on its use in animals. Pregnancy monitoring in sheep can reduce both maternal and lamb mortality rates. Quantitative and objective evaluation of the cervix and vulvar lips in pregnant ewes may help determine the presence of a healthy pregnancy and the timing of parturition. This study aimed to evaluate the changes in cervical diameter, vulvar thickness, and shear wave speed (SWS) of the cervix and vulvar lips during the days preceding normal parturition and on the day of postpartum in Kivircik ewes.MethodsUltrasonographic measurements of the 12 ewes included in the study were taken daily, starting 5 days before expected parturition and continuing until 6–12 h postpartum (Day 0). The SWS of the cervix was measured in two different regions: near the internal os of the cervix (IOC) and near the external os of the cervix (EOC). Time-dependent differences in the evaluated cervical and vulvar parameters were assessed using the general linear model and repeated measures ANOVA. When statistical significance was detected, the LSD pairwise comparison test was used to determine the significance of differences in the investigated parameters across the evaluation days.ResultsThe highest cervical diameter was recorded on Day −1. Time-dependent differences in mean SWS values were significant for the IOC but insignificant for the EOC. The mean SWS value of the IOC on Day −1 (2.29 ± 0.13 m/s) was lower than the values on all other evaluation days. The mean SWS value of the IOC on Day 0 was higher than the values on Days −1, −2, and −3. The thickness of the vulvar lips on Day −1 was similar to that on Day 0, but both were higher than the thickness measured on all other evaluation days. The mean SWS value of the vulvar lips on Day −1 was similar to those on Days −2 and 0, but it was lower than the value on Days −5, −4, and −3.ConclusionIn conclusion, it was possible to identify changes in the cervix and vulvar lips during the days preceding normal parturition and on the day of postpartum in ewes. Final ripening of the IOC and edema of the vulvar lips were reflected by decreased SWS values. Marked uterine contractions persisting during the postpartum period resulted in increased SWS values at the IOC.